NILAI RERATA TES SKRINING NEUROPSIKOLOGI LURIA NEBRASKA STLNNB SEBAGAI PEMERIKSAAN FUNGSI KOGNITIF PADA POPULASI NORMAL - Lani Septia*, Silvia F. Lumempow**, Diatri N.Lastri**, Herqutanto*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION STLNNB IS A MULTIDOMAIN COGNITIVE SCREENING TOOL THAT CAN BE APPLIED START FORM 13 YEARS IN 20 MINUTES THIS STUDY IS AIMED TO GET THE PERFORMANCE OF STLNNB IN NORMAL POPULATION ACCORDING TO DEMOGRAPHIC FACTORS SUCH AS AGE SEX AND EDUCATION